2018
DOI: 10.1002/jmri.26042
|View full text |Cite
|
Sign up to set email alerts
|

Total choline quantification measured by 1H MR spectroscopy as early predictor of response after neoadjuvant treatment for locally advanced breast cancer: The impact of immunohistochemical status

Abstract: 1 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2018;48:982-993.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A recent study showed the use of single‐voxel 1 H MRS to predict the response of chemotherapy treatment at 24–72 hours after administration of the first cycle of chemotherapy . In this study, the measured tCho levels in the tumor‐containing voxels were used to differentiate patients who responded to treatment . This study also emphasized the importance of an early assessment of response to anthracyclines in order to facilitate clinical decision‐making for further treatment …”
Section: Detection Of Gpc As a Biomarker Of Therapy Responsementioning
confidence: 95%
See 1 more Smart Citation
“…A recent study showed the use of single‐voxel 1 H MRS to predict the response of chemotherapy treatment at 24–72 hours after administration of the first cycle of chemotherapy . In this study, the measured tCho levels in the tumor‐containing voxels were used to differentiate patients who responded to treatment . This study also emphasized the importance of an early assessment of response to anthracyclines in order to facilitate clinical decision‐making for further treatment …”
Section: Detection Of Gpc As a Biomarker Of Therapy Responsementioning
confidence: 95%
“…1 H MRS assessment of the tCho signal in breast cancer patients, which was achieved with water and fat suppression sequences, measured prior to the start of chemotherapy and after the three cycles of chemotherapy, has shown potential for predicting the response to chemotherapy (Figure ) . A recent study showed the use of single‐voxel 1 H MRS to predict the response of chemotherapy treatment at 24–72 hours after administration of the first cycle of chemotherapy . In this study, the measured tCho levels in the tumor‐containing voxels were used to differentiate patients who responded to treatment .…”
Section: Detection Of Gpc As a Biomarker Of Therapy Responsementioning
confidence: 99%
“…However, it is worth noting that consistent elevations in PMEs and tCho have been observed in a wide range of tumors, including brain, prostate, lung, skin, ovarian, and breast . As a means to monitor therapeutic response, tumor choline levels have been measured using MRS in animal and human tumors with mixed results, at least partly due to the technical difficulties associated with acquiring choline spectra on a background of high fat in normal breast tissue. The picture is further complicated because ChoK is not the only enzyme that contributes to PC accumulation; it can be produced directly by the actions of PLC on PtdCho, or by the hydrolysis of GPC as a source of additional choline for subsequent phosphorylation.…”
Section: Imaging Metabolic Lipid Changesmentioning
confidence: 99%
“…Our work was based on retrospective postprocessing of data acquired from a prospective, nonrandomized, singe center, diagnostic study initiated in our institution from the same authors (EudraCT number: 2011‐006259‐12/ BECT number: B079201111884/ http://clinicaltrials.gov) from February 2013 to January 2017. The results from the initial study have been previously published but our current work adds the PRM analysis of the data. Patients were included in the prospective study according to: female gender, age ≥18 years; previously untreated invasive ductal or lobular breast cancer or any breast cancer ≥2 cm with an indication for neoadjuvant chemotherapy and adequate renal function.…”
Section: Methodsmentioning
confidence: 99%
“…Several magnetic resonance imaging (MRI)0based biomarkers have been assessed with the objective of predicting as early as possible the response to neoadjuvant treatment. These include using quantitative parameters extracted from dynamic contrast‐enhanced (DCE)‐MRI such as K trans and K ep , either by using diffusion‐weighted imaging (DWI) or choline quantification (tCho) . These biomarkers are generated by averaging certain imaging properties from a region of interest (ROI), importantly without taking into account any spatial information.…”
mentioning
confidence: 99%